(untitled) (Journal of the College of Basic Education, 2022)
The aim of this study was to estimate the intoxicated hemoglobin in patients with major and minor Mediterranean anemia, compared with the control group, in order to investigate the possibility of using it as a guide for comparison with the levels of the control group.